Privatization Priorities of Iranian Football Clubs from the Perspective of Experts - Javad Shahlaee; Fatemeh Ghorbanalizadeh Ghaziani (The Society of Aging and Physical Activity (SAPA), 2015)
Today, the role of government is considered so much precise regulations, foresight and initiative of the public sector in the economy can trigger market growth. But usually because the private sector activity is affected by interactions of the market and government, markets' development process is slow and governmental clubs have become a consumer of financial resources by their inefficient function and do not allow the private sector to carry out economic productive activities in a competitive environment. Under these conditions, privatization puts forward a clear and obvious solution. The study purpose is applied and data collection method is a descriptive survey. The study population consists of football managers, university professors of physical education and sports' experts. In order to determine factors' priority, Mean Rank technique from AHP, TOPSIS, SAW ranking technique was used and software Excel and Expert choice were used to identify the challenges. According to the findings of the present study, the most important challenges are prioritizing, political-legal challenges, economic challenges, socio-cultural challenges and technological challenges. Privatization with no program and step was the most important legal and political challenge, lack of importance of sport in socio-economic development programs' set was the most important socio-cultural challenge, non-realization of television broadcast as a source of income was the most important criterion of economic challenge and lack of facilities granted by the government to the private sector, such as electricity and gas was considered the most important criterion of technological challenge.